Rabbit feeding and nutrition - Cheeke, Peter R. (Animal feeding and nutrition., 1987)
During the past few years, considerable research has been undertaken on rabbit nutrition. Rabbit producers, feed manufacturers, animal nutritionists, and others interested in rabbit production will find this book to be the new authority. Comprehensive and up-to-date, the book evaluates new information on such topics as protein digestion and requirements, nutrition/disease interrelationships, feeding behavior, and nutrional factors involved in enteritis.